Perceptions on ozonation water treatment use: an alternative idea for ASEAN water resource sustainability - Siriwat Potivejkul (2020)
Ozonation (or ozonisation) is a chemical water treatment technique based on the infusion of ozone into water. As early as 1893, this process was used in Europe for the treatment of drinking water and as recently as 2014, the most modern ozone water treatment facility in the world was brought online to protect the waters of Switzerland’s Lake Geneva. However, studies vary widely in conditions leading to ozone technology use, and the subsequent factors concerning its effectiveness. From a population of 7,006 Thai industrial estate companies, a sample of 500 executives, managers, and engineers was drawn which completed an 80-item survey which was analysed by use of a structural equation model using LISREL 8.72. Results showed that acceptance had the greatest influence on ozonation treatment technology use, while the remaining five latent variables (ranked in importance) included curiosity, provisional trial, testing, cognizance, and strategy.